PENGARUH FAKTOR DEMOGRAFIS TERHADAP INTENSITAS MENONTON PROGRAM BERITA TVONE DIKALANGAN MASYARAKAT KECAMATAN PEKANBARU KOTA - Putri, Marissa; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Demographic factors consist of age, gender, level of education, occupationand income level is one of factor that is easily measured to see the pattern ofaudience watching television. Persons age affects the availability of leisure time andthe choice of media content. Likewise income level person, education and higherprofessional occupations also result in option of different content, that is moreinformational content or content that is further supported by the values of thedominant culture and education. The purpose of this research to know influence ofdemographic factors to the intensity on watching news program in TVOne. Thisresearch used Dennis McQuailâs Audience Composition Theory.Itâs a quantitative research with explanatory type. The populations in thisresearch are 100 samples citizens of Pekanbaru Kota subdistrict which is determinedby using Slovin formula. The Accidental Sampling is used on researchâs sampling,with Multiple Linear Regression data analysis.Hypothesis test shows that each of age, gender, level of education, occupationand income level variable influence the intensity on watching news program with asignificance value less than 0.05, this means that Ho is refused and Ha is acceptedbut income variable not influence with value more than 0,05 this means that Ho isaccepted. And demographic factors simultaneously influent the intensity on watcingnews program with significant value on 0.000 or less than 0.05, this means that Ho isrefused and Ha is accepted. The result shows that respondents intensity on watchingnews program in TVOne is high until very high and there is effect of demographicfactors with intensity on watching news program. This research also shows thatrespondents, age 30 years old or more, male, senior high school until high leveleducation, formal worker and middle-high income have high level intensity onwatching news program in TVOne.Keywords : Demographic factors,Watching intensity, News program, TVOne